Association genetics of oleoresin flow in loblolly pine: discovering genes and predicting phenotype for improved resistance to bark beetles and bioenergy potential. Issue 1 (28th March 2013) - Westbrook, Jared W.; Resende, Marcio F. R.; Munoz, Patricio; Walker, Alejandro R.; Wegrzyn, Jill L.; Nelson, C. Dana; Neale, David B.; Kirst, Matias; Huber, Dudley A.; Gezan, Salvador A.; Peter, Gary F.; Davis, John M.
Summary Rapidly enhancing oleoresin production in conifer stems through genomic selection and genetic engineering may increase resistance to bark beetles and terpenoid yield for liquid biofuels. We integrated association genetic and genomic prediction analyses of oleoresin flow (g 24 h−1) using 4854 single nucleotide polymorphisms (SNPs) in expressed genes within a pedigreed population of loblolly pine (Pinus taeda) that was clonally replicated at three sites in the southeastern United States. Additive genetic variation in oleoresin flow (h2 ≈ 0.12–0.30) was strongly correlated between years in which precipitation varied (ra ≈ 0.95), while the genetic correlation between sites declined from 0.8 to 0.37 with increasing differences in soil and climate among sites. A total of 231 SNPs were significantly associated with oleoresin flow, of which 81% were specific to individual sites. SNPs in sequences similar to ethylene signaling proteins, ABC transporters, and diterpenoid hydroxylases were associated with oleoresin flow across sites. Despite this complex genetic architecture, we developed a genomic prediction model to accelerate breeding for enhanced oleoresin flow that is robust to environmental variation. Results imply that breeding could increase oleoresin flow 1.5‐ to 2.4‐fold in one generation.